Respiratory Therapy for Acute Respiratory Distress Syndrome in Cardiosurgical Patients - T. V. Zagorodnyaya; A. N. Korniyenko; M. V. Ketskalo (Общая реаниматология)
The purpose of the present investigation was to improve the outcomes of intensive care in patients with acute respiratory distress syndrome after cardiac surgery under extracorporeal circulation.Materials and methods. Respiratory therapy was analyzed in 43 patients with acute respiratory distress syndrome after surgery under extracorporeal circulation. According to the procedure of artificial ventilation (AV), the patients were divided into 2 groups: 1) those who had undergone routine tracheal intubation (n=23) AND 2) THOSE who had received noninvasive intubation through a nasal mask (n=20). The respiratory parameters, blood gas composition, central hemodynamic parameters, respiratory support time, and the pattern of complications were analyzed.Results. Noninvasive artificial ventilation permits one to make the patients active in earlier periods and take a spontaneous breath, recovers the respiratory index earlier, reduces the level of positive end-expiratory pressure, the frequency of infectious complications of the tracheobronchial tree, and length of stay in an intensive care unit as compared with endotracheal AV.Conclusion. The findings suggest that noninvasive AV is highly effective and yields better results of treatment in patients with acute respiratory distress syndrome.